Socio-demographic and household characteristics of unmarried mothers as risk factors for low birthweight and infant death in Northern Ireland - Casson, Karen; Given, Joanne; Rosato, Michael; Bunting, Brendan; Gray, Ann Marie (International Journal of Population Data Science, 2018)
Background Compared to married mothers, mothers who are not married when they register their child’s birth are at increased risk of having a low birthweight baby and infant death. Having a partner protects women from poor pregnancy outcomes to some extent but those who are living with, but not married to, their partner still do less well than those who are married. As it does not appear to be marriage itself which is protective, other factors such as maternal education and smoking, and household characteristics, such as accommodation type and familial support in the household, need to be examined. Aim To explore the individual socio-demographic and household characteristics that are associated with low birthweight and infant death among unmarried mothers. Methods A population based cohort study will be conducted through the Administrative Data Research Network based on all registered live births 2010-2016 to women resident in Northern Ireland (NI). General Register Office (GRO) birth records will be linked to the NI Maternity System and GRO infant death data to identify low birth weight (primary) and infant death (secondary) outcomes. Maternal individual socio-demographic and household characteristics will be provided through linkage to the 2011 census (ethnicity, highest level of education, support from family members living in the household); Enhanced Prescribing Database (maternal mental health prescriptions); 2010 NI Multiple Deprivation Measure (area level deprivation, including income and education domains, for the mother’s home address at the time of birth) and Valuation and Lands Agency Rating List (capital value of property of mother’s address). Descriptive statistics and logistic regression will be used for the analysis. Impact It is anticipated the findings will reduce the public health burden of low birthweight babies by directing interventions to targeted groups of mothers.